2019
DOI: 10.1111/pce.13553
|View full text |Cite
|
Sign up to set email alerts
|

Potassium mediates coordination of leaf photosynthesis and hydraulic conductance by modifications of leaf anatomy

Abstract: Typical symptoms of potassium deficiency, characterized as chlorosis or withered necrosis, occur concomitantly with downregulated photosynthesis and impaired leaf water transport. However, the prominent limitations and mechanisms underlying the concerted decreases of leaf photosynthesis and hydraulic conductance are poorly understood. Monocots and dicots were investigated based on responses of photosynthesis and hydraulic conductance and their components and the correlated anatomical determinants to potassium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Interestingly, recent modeling and experimental studies found S m , T cw and membrane permeability also influence the water transport efficiency through mesophyll tissues (Xiong et al, 2017). However, Lu et al (2019) did not find such relationships; in fact, they observed intraspecific relationships between the fraction of the mesophyll cell wall adjoining other cell walls (f cm ) and K ox among four crop species subjected to different K supplies. This result would suggest a major role of cell connectivity across tissues in the apoplastic pathway, contrasting with the greater vapor phase that could be associated with S m , which reflects cell exposure to intercellular spaces and thus increased surface for water evaporation along the water pathway.…”
Section: Links Between K Leaf and Co 2 Diffusionmentioning
confidence: 90%
See 3 more Smart Citations
“…Interestingly, recent modeling and experimental studies found S m , T cw and membrane permeability also influence the water transport efficiency through mesophyll tissues (Xiong et al, 2017). However, Lu et al (2019) did not find such relationships; in fact, they observed intraspecific relationships between the fraction of the mesophyll cell wall adjoining other cell walls (f cm ) and K ox among four crop species subjected to different K supplies. This result would suggest a major role of cell connectivity across tissues in the apoplastic pathway, contrasting with the greater vapor phase that could be associated with S m , which reflects cell exposure to intercellular spaces and thus increased surface for water evaporation along the water pathway.…”
Section: Links Between K Leaf and Co 2 Diffusionmentioning
confidence: 90%
“…Recently, the coordination of K leaf and mesophyll conductance to CO 2 (g m ), another major photosynthetic limitation factor (for review, see Flexas et al, 2012), across species and/or genotypes was suggested by several studies (Flexas et al, 2013;Xiong et al, 2017Xiong et al, , 2018Lu et al, 2019; Figure 2c). The g m accounts for the apparent diffusion efficiency of CO 2 from substomatal cavity through mesophyll cell components into the chloroplasts where biochemical assimilation occurs.…”
Section: Links Between K Leaf and Co 2 Diffusionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are suggested to be correlated across different plant species (Flexas et al, ) and across different genotypes within a single plant species (Xiong et al, ). Their coordination is also present when plants are subjected to drought stress (Wang et al, ), and potassium deficit (Lu et al, ). The coordination between g m and K leaf is important to the balance of plant carbon gain and water loss.…”
Section: Introductionmentioning
confidence: 99%